Shared Decision Making Surrounding the Role of Paraesophageal Hernia Repair in Elderly Patients. Issue 1 (March 2022) - Merriman, Nathan; Dunbar, Kerry; Litle, Virginia R.
Paraesophageal hernias in older patients can present a management dilemma for the patient, surgeon, and gastroenterologist. "Watch and wait" or operate are the 2 choices influenced by age. Shared decision making in the discussion of options is necessary to reflect a respect for the patient's values. A team-based approach involving the patient and family provides a clear clinical pathway and connection across primary care, gastroenterology, and foregut surgery.